Responsabilidad de los Estados frente a los daños ocasionados por objetos espaciales : el problema de los desechos espaciales frente al tema de la responsabilidad (2017)
"Extending human presence beyond the frontier of the earth's atmosphere meant that the problems and conflicts of every corner inhabiting man were found in an area previously untouched. Thus, law would soon take action, seeking regular, as possible at that time, scenarios where accidents or errors could generate huge material costs or human lives. This is how the liability regime for damages caused by space objects arises. The present work will seek to make a tour of the aspects of this unique regime of responsibility, seeking to conclude with a question in front of it; Is the regulation of liability for damage caused by space objects in space sufficient?".-- Tomado del Formato de Documento de Grado.